Educational Values in the Kaba Minangkabau Text "Anggun Nan Tongga Si Magek Jabang" - Ita Khairani; Andin Nur Sinaga (Lakhomi Journal Scientific Journal of Culture, 2020)
This study aims to determine the values of education in the text of the Minangkabau Kaba Manuscript "Anggun Nan Tongga Si Magek Jabang" with the study of sociology of literature. The type of research used is qualitative research with descriptive research methods. The purpose of this study was to describe the values of education in Kaba Minangkabau "Anggun Nan Tongga Si Magek Jabang". The data collection technique used to obtain data was by searching for literature and analyzing the story of Kaba Minangkabau "Anggun Nan Tongga Si Magek Jabang". From the research results, it is obtained the values of religious, moral, social and cultural education. Educational values that really dominate are the values of religious and moral education. From the results of data analysis, Kaba Minangkabau was not only a public entertainment at its time.